Can ChatGPT be integrated into Blended Learning in Science: A Systematic Literature Review - Afif Rusdiawan; Enny Hasriyani; Armein Lusi Zeswita; Ruth Rize Paas Megahati S; Nugroho Susanto (Jurnal Penelitian Pendidikan IPA, 2024)
Success requires highly qualified teachers who use their skills and assessment tools to diagnose learner needs, and then design targeted instruction with available resources. Only in this way can the integration of ChatGPT in blended learning be transformational, when teaching does not reflect traditional practices but is a series of dynamic experiences in the hands of students. Where the research aims to examine the Integration of ChatGPT in Blended Learning: A Systematic Literature Review. The review was conducted based on state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guidelines. The results of this research explain that there are 4 types of characteristics of Blended Learning, namely Combining Various Delivery Methods, Combining Direct Teaching, and Combining Effective Teaching Methods and Learning Styles, Teachers and Parents Have the Same Role. Some of the benefits of Blended Learning are More Flexible, Effective Learning Results, Increasing Student Interaction and Involvement, Able to Increase Learning Satisfaction, Student Participation Becomes More Active, and costs and Time. Categories of Use of Technology (ChatGPT) in Blended Learning are Managed learning, regulated learning, collaborative learning, and authentic learning